Editor's Introduction to the Summer 2018 Isue - Linda Essig (Artivate, 2018)
Welcome to the Summer 2018 issue of Artivate: A Journal of Entrepreneurship in the Arts. This is a very special debut issue, featuring the work of three emerging scholar/artists.